Submitral aneurysm: An antenatal diagnosis - Neeraj Awasthy; Savitri Shrivastava (Wolters Kluwer Medknow Publications, 2013)
We describe the echocardiographic features of submitral aneurysm in a 26 week old fetus. The diagnosis was confirmed on neonatal echocardiography.